A Conceptual study on E-marketing & Its technologies - Saxena, AKash; Sharma, Sonal (International Journal of Psychosocial Rehabilitation, 2020)
E-Marketing is the blessing of any company as well as the customer. It makes life much more comfortable. Each individual is being benefited to take advantage of E-marketing. Nowadays, every business is doing online-based, e- based, and using online marketing tools keeps a position in the consumer mind. The entire customer is now online-oriented. This study explores and explains what e-marketing is, what the present marketing trend is, and what the marketing field's future holds. The article discovered and concluded that e-marketing is the way of the future since it has been positively influenced by current technological advancement, which has made the usage of smartphones and gadgets a requirement.